Understanding digitalization and educational change in school by means of activity theory and the levels of learning concept - Pettersson, Fanny (Education and information technologies, 2021)
As shown in research and practice digitalization processes are many times limited to implementation of digital technologies without pedagogical and organizational change. In this study it is argued for a broader perspective on the concept of digitalization, viewing it as a process involving change and transformation in different stages and several organizational levels. Based on cultural–historical activity theory and the concept of levels of learning, this study will elaborate on the concept of digitalization as well as how schools are dealing with digital and educational change. Two schools known for their large-scale digitalization processes are analyzed. In the analysis, it is indicated that the object of digitalization harbors an idea that influence how digitalization is planned for and enacted within the school organization. How schools conceptualized—what is theoretically and practically meant by digitalization—influence how they plan their budget, professional development, and organizational change. With this backdrop, it is a concluded need for explicit discussions and conceptual clarifications on what digitalization is and what it involves in different school contexts.